Faktor Penyebab Rendahnya Kedisiplinan Siswa di Sekolah SMAN 2 Tilatang Kamang - Ulfazila Afratul Islamy; Fadilla Yusri; Sartika Anggarini (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Discipline is a condition where individuals obey and implement rules, regulations, laws and regulations relating to self-discipline without any assistance from certain parties. However, many students today do not obey the rules taught at school and do so politely. Based on current phenomena, researchers are interested in knowing the factors that cause the decline in student discipline at SMAN 2 Tilatang Kamang. The method used in this research is a qualitative descriptive method. In terms of obeying school regulations, students are expected to understand which disciplines need to be obeyed. In addition, the guidance given to them is not always followed by students. Because friends break these rules, other students will have a bad impact. Thus, SMAN 2 Tilatang Kamang is still classified as having a rather low level of discipline. This is shown by the number of students who disrupt routines such as coming late to school. Even though schools have provided training to students regarding discipline, students' self-awareness is very important.